2017
DOI: 10.1177/1010539516689695
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consequences and Social Issues After the Fukushima Disaster

Abstract: The Great East Japan Earthquake and subsequent nuclear power plant accident caused multidimensional and long-term effects on the mental health condition of people living in Fukushima. In this article, focusing on the influence of the nuclear disaster, we present an overview of studies regarding the psychosocial consequences of people in Fukushima. Studies revealed that the experiences of the explosions at the plant as well as the tsunami are deeply embedded in their memory, leading to posttraumatic responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 46 publications
3
92
1
2
Order By: Relevance
“…Examining perceived stigma and self-stigma of people affected by Japan's disaster provides an opportunity to better understand the impacts of mass media and interpersonal communication in crisis communication. Reducing miscommunication, confusion, and a media-produced public stigma might lower self-stigma and the long-term negative psychosocial effects that follow (Maeda & Oe, 2017). Crisis management relies on dissemination of accurate information.…”
mentioning
confidence: 99%
“…Examining perceived stigma and self-stigma of people affected by Japan's disaster provides an opportunity to better understand the impacts of mass media and interpersonal communication in crisis communication. Reducing miscommunication, confusion, and a media-produced public stigma might lower self-stigma and the long-term negative psychosocial effects that follow (Maeda & Oe, 2017). Crisis management relies on dissemination of accurate information.…”
mentioning
confidence: 99%
“…Looking back, I believe it is reasonable to assume that the series of tragedies Fukushima people experienced impacted their psychological well-being individually. For example, a survey conducted in Fukushima indicated that 21.6 percent were at risk of post-traumatic stress disorder (PTSD), which was significantly higher than the national average of 3 percent (Maeda, Ueda, Nagai, Fujii, & Oe, 2016). However, I did not expect to find effects of trauma on my participants, as none of them claimed to have PTSD and all appeared to be socially functional.…”
Section: Encountering Traumamentioning
confidence: 93%
“…Such public worry can have a substantial impact on indirect public health effects (cf. Lyamzina, 2018;Maeda & Oe, 2017;Maeda, Lyamzina, & Ito, 2019;Sato & Lyamzina, 2018). Thus, considerate and well-informed risk communication strategies would produce more efficient and more humane results.…”
Section: Reactions To Radiation Risk Normal or Phobic?mentioning
confidence: 99%